2004
DOI: 10.12968/jowc.2004.13.9.26703
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SurePress Comfort: a new compression system for the management of venous leg ulcers

Abstract: This study was sponsored by ConvaTec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…10 The SurePress Comfort (ConvaTec) stocking kit was compared with a Comprilan (BSN) bandage. Compression in both groups was applied by professionals at intervals that were not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The SurePress Comfort (ConvaTec) stocking kit was compared with a Comprilan (BSN) bandage. Compression in both groups was applied by professionals at intervals that were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…However, as exemplified by three studies (176 patients) only 6.5% of randomized patients were unable to put on the stockings. 8,10,14 The proportion of patients not fit to handle stockings by themselves or with little help might well be larger in a real world situation. Third, critiques may say that bandages were inferior because materials and application techniques were inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the major limitation in the findings of the reviewed studies is the substantial heterogeneity itself among ulcer features (size and commencement duration). The inclusion of large ulcers with long durations in some of the reviewed studies and the inclusion of small ulcers with short durations in others is the most likely cause of the differences in the HT among the reviewed studies [27-36]. This result is in line with the observational study by Escaleira et al [38] who included ulcers varying in size from large to small and of durations from short to long and found that this accounted for a significant variance in HTs in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies that review the competency of the applicators, the consistency of the applied pressure was confirmed as one of the main factors that underline the variability in the baselines and HTs of bandage studies of strength in most of the reviewed studies [27-36]. Highly competent applicators applied and maintained the most consistent pressure, which in turn shortened HT [27-31, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation